2015
DOI: 10.1186/s13293-015-0037-7
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in Sjögren’s syndrome: a comprehensive review of immune mechanisms

Abstract: Autoimmune diseases (ADs) are estimated to affect between 5 and 8 % of the US population, and approximately 80 % of these patients are women. Sjögren’s syndrome (SS) is an AD that occurs predominately in women over men (16:1). The hallmark characteristic of SS is diminished secretory production from the primary exocrine gland and the lacrimal or salivary glands resulting in symptoms of dry eye and mouth. The disease is believed to be mediated by an inflammatory and autoantibody response directed against saliva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
95
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(110 citation statements)
references
References 136 publications
9
95
0
6
Order By: Relevance
“…(Christian et al, 2009; Ford and Stowe, 2013; Glaser et al, 1991; Stowe et al, 2010) Because depression(Andersson et al, 2015; Euesden et al, 2017) and EBV(Niller et al, 2008) are both linked to certain autoimmune disorders (e.g. systemic lupus erythematosus) known to occur more frequently in females,(Brandt et al, 2015; Dunn et al, 2015; Ngo et al, 2014) further research testing causal pathways and the role of sex hormones in EBV reactivation and immune irregularities among adolescents is warranted.…”
Section: 0 Discussionmentioning
confidence: 99%
“…(Christian et al, 2009; Ford and Stowe, 2013; Glaser et al, 1991; Stowe et al, 2010) Because depression(Andersson et al, 2015; Euesden et al, 2017) and EBV(Niller et al, 2008) are both linked to certain autoimmune disorders (e.g. systemic lupus erythematosus) known to occur more frequently in females,(Brandt et al, 2015; Dunn et al, 2015; Ngo et al, 2014) further research testing causal pathways and the role of sex hormones in EBV reactivation and immune irregularities among adolescents is warranted.…”
Section: 0 Discussionmentioning
confidence: 99%
“…One of the primary clinical features of SS is that the disease is closely linked to sex, with roughly 90% of cases being diagnosed among females 3,4 ; however, no underlying sexual differences have been identified that might account for the degree to which females are more vulnerable to the disease. Specifically, only vague and largely descriptive references to hormonal differences have been offered to date 64‐66 . The data shown here offers an indication of potential underlying mechanisms that may help shed light on the vastly differing disease patterns between sex.…”
Section: Discussionmentioning
confidence: 98%
“…According to the National Institute of Health (NIH), 1 systemic autoimmune diseases (SADs) affect 23.5 million people in United States (prevalence of 8%). The proportion of primary Sjogren's syndrome (pSS) among patients affected by systemic autoimmune diseases (SADs) remains debated, but prevalence of the disease is estimated around 0.05%.…”
Section: Introductionmentioning
confidence: 99%